Happy Birthday : A Novel - Steel, Danielle (New York : Delacorte Press, 2011)
"Valerie Wyatt is at the top of her game--she has parlayed her talent for entertaining and home decorating into a multimedia empire, and her name is synonymous with class and exquisite taste. And yet, though she has achieved enviable professional success, her ambition and hard work have given her little room for a personal life. She is divorced, and though she has a strong relationship with her daughter, she finds herself alone as her 60th birthday approaches. Valerie's daughter, April, is also a dynamo in her chosen field. A top-notch chef, she owns her own restaurant--a cozy place that dishes up both comfort food and rare delicacies. The restaurant is a smashing success, and April devotes herself to it body and soul. Like her mother, she values professional success more than romance, and she cannot find any room for a man in her life as her 30th birthday grows nearer. The closest she has come to a relationship in years is an ill-advised one night stand. Jack Adams is a famous former NFL player, who is now an immensely successful sportscaster. He is also an incorrigible womanizer, who makes a habit of bedding models who are half his age. Nearing age 50 he begins to wonder if his wild ways still suit him, or if it's finally time to grow up. These three driven professionals share the same birthday. And this year, the day that they share will prove to be one that changes their lives forever. Their birthday will set into motion a dramatic series of events--danger, adventure, laughter, heartbreak, and joy...and, ultimately, the most fulfilling "birthday gift" of all"--
Keywords: Businesswomen -- Fiction; Mothers and daughters -- Fiction; Sportscasters -- Fiction; FICTION / General; Love stories